Evaluation of the Effectiveness of Two Automated Room Decontamination Devices Under Real-Life Conditions - Knobling, Birte; Franke, Gefion; Klupp, Eva M.; Belmar Campos, Cristina; Knobloch, Johannes K. (Frontiers in Public Health, 2021)
To evaluate the effectiveness of automated room decontamination devices, a common aerosolized hydrogen peroxide (aHP) and a recent gaseous ozone based device, which produces the disinfectant reagent without any consumable expect water and atmospheric oxygen, were tested in four independent experiments under real-life conditions. Therefore, 22 contaminated surfaces were positioned in a patient room with three parts. After decontamination process bacteria were recovered and quantitative cultures were produced such as reduction factor was calculated. According to manufactures instructions the ozone based device shows a bactericidal effect (log10 > 5), whereas aHP system achieves a reduction of realistic bioburden (log10 2). After increase the exposure time to 30 min, the aHP device reached a bactericidal effect too. Nevertheless, our results show, that further research and development is necessary, to get knowledge about toxicity, efficacy and safety by using in complex hospital conditions and achieve meaningful integration in cleaning procedures, to reach positive effects on disinfection performance.